2009
DOI: 10.1002/ange.200903063
|View full text |Cite
|
Sign up to set email alerts
|

Plagiarizing Proteins: Enhancing Efficiency in Asymmetric Hydrogen‐Bonding Catalysis through Positive Cooperativity

Abstract: A new twist for a fold: Conformationally well‐defined thiourea catalysts, like that shown, stabilized by intramolecular hydrogen bonds demonstrate cooperative ligand–receptor binding. This conformation leads to significantly enhanced catalytic efficiency, resulting in higher turnover rates and lower catalyst loading whilst maintaining high enantioselectivity in a model reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…As a result, only one of the hydrogen‐bond donors in the catalyst may be used for the activation of the electrophile,4a thus reducing the level of activation of the electrophile. We reasoned that the presence of an intramolecular hydrogen bond5 could provide significant improvement in the hydrogen‐bond‐donor capacity of the thiourea moiety through cooperative effects,6 as already demonstrated by Smith and co‐workers (catalyst C ; Scheme ) 5d…”
Section: Methodsmentioning
confidence: 82%
“…As a result, only one of the hydrogen‐bond donors in the catalyst may be used for the activation of the electrophile,4a thus reducing the level of activation of the electrophile. We reasoned that the presence of an intramolecular hydrogen bond5 could provide significant improvement in the hydrogen‐bond‐donor capacity of the thiourea moiety through cooperative effects,6 as already demonstrated by Smith and co‐workers (catalyst C ; Scheme ) 5d…”
Section: Methodsmentioning
confidence: 82%
“…Oligomers consisting of N , N ′‐linked urea bridging units are receiving increasing attention as folding backbones 9. 1520 Peptidomimetic oligoureas belonging to the γ ‐peptide lineage,21 (‐NH‐CH(R i )‐CH 2 N′H‐CO) n ‐, have a remarkable propensity to fold into helical secondary structures in solution2226 and show promise for interaction with biologically relevant targets 27. 28 Compared to γ‐peptides,5, 29, 30 helix stabilization in oligoureas is promoted by the presence of additional backbone conformational restriction and H‐bond donor sites.…”
mentioning
confidence: 99%
“…31, 38 Our study also demonstrates the robustness of the folding process: four acyclic residues are sufficient to drive complete helix formation with all complementary H‐bonding sites being satisfied. Overall, this crystallographic data set provides the ground for the structure‐guided development of urea foldamers with function, such as recognition of biomolecules and catalysis,20, 39, 40 and also for the elaboration of new tertiary and quaternary structural motifs.…”
mentioning
confidence: 99%
“…The behavior of the receptor 2 proves that reinforced molecular recognition can be achieved by much simpler systems than was initially thought. In addition it can also be concluded that reinforcement is not only a valid tool to improve receptors but also for favoring chiral discrimination, thus paving the way to a novel concept for asymmetric catalysis 33. 34 It is worth mentioning that up until now all the reported methods for improved chiral recognition are based either on a more rigid receptor or on bulkier chiral auxiliaries.…”
Section: Methodsmentioning
confidence: 99%